(untitled) (Bangladesh Journal of Public Administration, 2019)
In the present context of the fourth Industrial Revolution, science education is considered as the appropriate tool for the development of a nation. Accordingly, the government of Bangladesh has laid significant emphasis on science and technology education as a gateway to development with an aspiration to build a „Digital Bangladesh‟ and to attain the status of a middle-income country by 2021. However, contrasting to a large number of government initiatives, a declining scenario of enrollment in science groups at the secondary level has been reported for nearly a decade. This situation is likely to be worse in rural areas as it was evident from a visit to Chakaria Upazila of Cox‟s Bazar. Drawing attention to the underlying problems of science education, this study attempts to provide an account of the present scenario of science enrollment at secondary school level in the rural Bangladesh, and identifies the factors responsible for the enrollment pattern. The ten years‟ trend analysis on science group enrollment provided a clear picture of declining scenario since 2010. Compared to the other two groups of Business and Humanities, preferences to be enrolled in the Science group at secondary level steadily showed a marked decrease from 2009 to 2018. Complexity and volume of the science syllabus creating “Science Fear”, weak teaching capacity, shortage of science and mathematics teachers, scarcity of teaching materials and paucity of laboratory equipment were found to be the key factors responsible for declining science enrollments in the secondary level of rural Bangladesh.